Visual Hand Recognition in Hand Laterality and Self-Other Discrimination Tasks: Relationships to Autistic Traits and Positive Body Image - Kuroki, Mayumi; Fukui, Takao (Frontiers in Psychology, 2020)
In a study concerning visual body part recognition, a “self-advantage” effect, whereby self-related body stimuli are processed faster and more accurately than other-related body stimuli, was revealed, and the emergence of this effect is assumed to be tightly linked to implicit motor simulation, which is activated when performing a hand laterality judgement task in which hand ownership is not explicitly required. Here, we ran two visual hand recognition tasks, namely, a hand laterality judgement task and a self–other discrimination task, to investigate i) whether the self-advantage emerged even if implicit motor imagery was assumed to be working less efficiently, and ii) how individual traits (such as autistic traits and the extent of positive self-body image, as assessed via the Autism Spectrum Quotient [AQ] and the Body Appreciation Scale-2 [BAS-2], respectively) modulate performance in these hand recognition tasks. Participants were presented with hand images in two orientations (i.e., upright [egocentric] and upside-down [allocentric]) and asked to judge whether it was a left or right hand (an implicit hand laterality judgment task). They were also asked to determine whether it was their own, or another person’s hand (an explicit self–other discrimination task). Data collected from men and women were analyzed separately. The self-advantage effect in the hand laterality judgment task was not revealed, suggesting that only two orientation conditions are not enough to trigger this motor simulation. Furthermore, the men’s group showed a significant positive correlation between AQ scores and reaction times (RTs) in the laterality judgement task, while the women’s group showed a significant negative correlation between AQ scores and differences in RTs and a significant positive correlation between BAS-2 scores and dprime in the self–other discrimination task. These results suggest that men and women differentially adopt specific strategies and/or execution processes for implicit and explicit hand recognition tasks.